Iron Supplementation in Anemic Pregnant Women: A Comparison of Different Prescription Options in Pakistan - Asma Kazi, Aisha Aziz, Shoaib Ahmed, Sabeena Umer, Shazia Roman, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background & objectives: Many pregnant women in Pakistan have iron deficiency anemia (IDA), a dietary deficit. It affects both the mother's and the foetal' health. Oral iron supplementation usually relieves IDA symptoms. Oral iron supplements are hazardous to the GI mucosa, and sensitivity is common. Poor therapeutic compliance leads to treatment failure. Ferrous ascorbate (FeA) and iron hydroxide polymaltose complex (IPC) reportedly improve gastrointestinal discomfort and increase patient compliance compared to ferrous sulphate (FS). These preparations reportedly improve hemoglobin levels and iron stores more quickly than FS. This analysis compared FS's efficacy and safety to IPC and FeA. Place of Study: Rashid Latif Medical College Lahore Duration of Study: February 2019 and October 2021 Methods: It was a randomized, parallel, open label, investigation among pregnant women of gestational age from 10 to 28 weeks with moderate anemia. Patients were randomly selected to receive either FS, IPC or FeA. They were then followed up for 3 months to look for improvement in the hemoglobin levels and other hematological indicators or any adverse drug response. Results: With the exception of 3 months, when the FeA group had a significantly higher hemoglobin level in comparison to the FS group (P <0.05), the hemoglobin levels were comparable across the three groups. The overall risk profiles for side effects were likewise equal across the research groups, with the exception of epigastric discomfort, which was more frequently reported in the FS group. Conclusions: The findings of the study indicated that FS, IPC, and FeA all have an efficacy and safety profile in the treatment of IDA associated with pregnancy that is comparable to one another. Keywords Anemia, ferrous ascorbate , ferrous sulphate ,iron hydroxide polymaltose ,pregnancy